PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP KEGIATAN DONOR DARAH - Lestari, Rafika Indy; Rosaliza, Mita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of this study was to determine the level and perception of University of Riau Students in Blood Donation Activities in a descriptive manner. The sampling technique in this study was simple random sampling for Riau University students who had donated, accidental sampling for Riau University students who had not yet donated. To better represent the researcher had taken a sample of 182 respondents, 91 respondents who have donated 91 respondents who have not donated. Data collection methods used to observation, questionnaire, documentation. This study uses quantitative methods, presented in tabular form and then given a description. This type of research is a descriptive quantitative research. The statistical test used is the validity and reliability test, and the processed data obtained using SPSS 24.0 for windows. The results of this study concluded that overall the level of perception of Riau University students who had donated or who had not yet donated. For those who have donated, they have two categories: high and medium, the high frequency category is 87 with a percentage (95.6%) and the moderate category is 4 with a percentage (4.4%). While those who have not donated have two categories, namely the low and moderate categories, for the low category of frequency 70 with a percentage (76.9%) and the moderate category 21 with a percentage (23.1%).Â Â Keywords: Perception, Students, Blood Donors.